Decreased levels of kynurenic acid in prefrontal cortex in a genetic animal model of depression. Issue 1 (13th July 2016) - Liu, Xi-Cong; Erhardt, Sophie; Goiny, Michel; Engberg, Göran; Mathé, Aleksander A.
Abstract : Objective: There is a growing interest in the role of kynurenine pathway and tryptophan metabolites in the pathophysiology of depression. In the present study, the metabolism of tryptophan along the kynurenine pathway was analysed in a rat model of depression. Methods: Kynurenic acid (KYNA) and 3-hydroxykynurenine (3-HK) were measured by high-performance liquid chromatography (HPLC) in prefrontal cortex (PFC) and frontal cortex (FC) in a rat model of depression, the Flinders Sensitive Line (FSL) and their controls, the Flinders Resistant Line (FRL) rats. In addition, KYNA was also measured in hippocampus, striatum and cerebellum. Results: KYNA levels were reduced in the PFC of FSL rats compared with FRL rats, but did not differ with regard to the FC, hippocampus, striatum or cerebellum. 3-HK levels in PFC and FC, representing the activity of the microglial branch of the kynurenine pathway, did not differ between the FSL and FRL strains. Conclusion: Our results suggest an imbalanced metabolism of the kynurenine pathway in the PFC of FSL rats.